Enhancing muscle strength and body composition after low-load resistance with blood flow restriction and hypoxia in untrained males - Arunya Buttichak; Chaiyawat Namboonlue; Sarawut Poca; Chaowanan Tanok; Sarocha Namboonlue (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación, 2025)
Introduction: High-intensity resistance training may elevate the risk of musculoskeletal injuries and hinder optimal performance execution.